Homo- and Heteronuclear meso,meso-(E)-Ethene-1,2-diyl-Linked Diporphyrins: Preparation, X-ray Crystal Structure, Electronic Absorption and Emission Spectra and Density Functional Theory Calculations - Locos, O.; Basic, Bruno; McMurtrie, J.; Jensen, P.; Arnold, D. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
Homo- and heteronuclear meso,meso-(E)-ethene-1,2-diyl-linked diporphyrins have been prepared by the Suzuki coupling of porphyrinylboronates and iodovinylporphyrins. Combinations comprising 5,10,15-triphenylporphyrin (TriPP) on both ends of the ethene-1,2-diyl bridge M(2)10 (M(2) =H(2)/Ni, Ni(2), Ni/Zn, H(4), H(2)Zn, Zn(2)) and 5,15-bis(3,5-di-tert-butylphenyl)porphyrinato-nickel(II) on one end and H(2), Ni, and ZnTriPP on the other (M(2)11), enable the first studies of this class of compounds possessing intrinsic polarity. The compounds were characterized by electronic absorption and steady state emission spectra, (1)H NMR spectra, and for the Ni(2) bis(TriPP) complex Ni(2)10, single crystal X-ray structure determination. The crystal structure shows ruffled distortions of the porphyrin rings, typical of Ni(II) porphyrins, and the (E)-C(2)H(2) bridge makes a dihedral angle of 50° with the mean planes of the macrocycles. The result is a stepped parallel arrangement of the porphyrin rings. The dihedral angles in the solid state reflect the interplay of steric and electronic effects of the bridge on interporphyrin communication. The emission spectra in particular, suggest energy transfer across the bridge is fast in conformations in which the bridge is nearly coplanar with the rings. Comparisons of the fluorescence behaviour of H(4)10 and H(2)Ni10 show strong quenching of the free base fluorescence when the complex is excited at the lower energy component of the Soret band, a feature associated in the literature with more planar conformations. TDDFT calculations on the gas-phase optimized geometry of Ni(2)10 reproduce the features of the experimental electronic absorption spectrum within 0.1 eV.